Vision based target tracking for autonomous vehicles - Jia, Zhen (2008)
In this thesis, problems such as data fusion, image features extraction, region of interest identi?cation, target state estimation and tracking have been closely studied. New methodologies have been developed for vision based target tracking for autonomous vehicles.